The Relationship Between Clinicopathological Features and Prognosis of 22 Cases of Tubular Breast Carcinoma - Lin Tian; Xiangchao Meng; Huiyan Si; Yue Qiu; Rui Qu; Hongye Chen (The Breast Journal)
Conclusion: Tubular breast carcinoma is a kind of tumor with a low malignant degree. The prognosis is significantly related to its HER-2 level, recurrence and metastasis, and postoperative comprehensive treatment by univariate analysis, in which HER-2 is an independent risk factor, postoperative comprehensive treatment is a protective factor, but postoperative recurrence and metastasis have nothing to do with the prognosis by the multivariate analysis.